Man and Nature in The Poetry of Dylan Thomas and Ted Hughes - Myšíková, Zuzana (Univerzita Pardubice, 2018)
The aim of this bachelor thesis is to provide an analysis of Ted Hughes's (1930 - 1998) and Dylan Thomas's (1914 - 1953) poetry. The first two chapters describe the theoretical background to ecocriticism and the subjects closely connected with the environmental criticism - anthropocentrism and anthropomorphism. There is also explained the use of pathetic fallacy a literary device used in the environmental literature. The third chapter of the thesis is divided into three subchapters and includes ecocritical comparative analyses of the selected poetry of Ted Hughes and Dylan Thomas. The results of the analyses are summarized in conclusion.
Člověk a příroda v poezii Dylana Thomase a Teda Hughese
Keywords: Hughes, Ted; Thomas, Dylan; animals; anthropocentrism; anthropomorphism; ecocriticism; nature; poetry; Hughes, Ted; Thomas, Dylan; zvířata; antoropocentrismus; antoropomorphismus; ekokritika; příroda; poezie